Assesment of antidermatophyte activity of oil from Curcuma longa L. in vitro - Mai Huong, Nguyen Thi; Cuong, Pham Viet; Kim Cuc, Nguyen Thi (Academia Journal of Biology, 2013)
Curcuma longa L. is a rhizomatous herbaceous perennial plant, and its essential oil showed antifungal, antibacterial, antioxydant, antivenom, and antitumor effects. The antidermatophytes of oil from turmeric was demonstrated. This study was carried out in order to evaluate inhibition activity of oil from Vietnamese turmeric against two strains dermatophyte, Trychophytol mentargrohytes and Candida albicans. The oil from Vietnamese turmeric was obtained by hydrodistillation method and its chemical composition was determined by GC/MS. By comparing with authentic reference compounds in mass spectra library Nist 98.1 and Wiley 275.L, 13 compounds of oil from Vietnamese turmeric were identified. The received results showed that, the oil is rich in turmerones (about 44%), which has been recognized as major constituent attributing to antimicrobial activity. By disc diffusion method, the antifungal activity of the turmeric essential oil against T. mentargrophyte and C. albicans was demonstrated. The MICs of the turmeric oil for T. mentargrophytes và C. albicans were 0.5%. The minimal killing time for C. albicans was 60 minutes and for T. mentargrophyte was 90 minutes after treatment with the turmeric oil.